TUTUR BHUWANA KOSA: KAJIAN SEMIOTIKA - Ni Wayan, Sri Santiati (Humanis; Volume 12. No.2. Agustus 2015, 2015)
Tutur Bhuwana Kosa is one of the oldest manuscript belonging to the group Wariga based calcification gedong Kirtya. A study of literature manifold said still a little done, therefore the subject of an interesting manuscript said to use the research object. Research on script  Tutur Bhuwana Kosa studied in terms of semiotics. But before examined in terms of semiotics first be analyzed in terms of structure. Analysis in terms of the structure aims to determine the structure of the build script oracle Tutur Bhuwana Kosa while semiotic analysis aims to analyze the meaning contained in the Tutur Bhuwana Kosa. Indirectly, this study may provide information to the public regarding the content Tutur Bhuwana Kosa. At the stage of data collection method used is the method of literature study and assisted interviewing method of recording and recording techniques. Phase of data analysis used descriptive analytic method. In presenting the results of the analysis used formal and informal methods, namely the presentation by using the symbol or symbols when needed and using ordinary words. Said structural analysis Tutur Bhuwana Kosa composed of Brahma Jnana Rahasyam and Rahasyam. Rahasyam Brahma is the first part contained in Tutur Bhuwana Kosa  that contains the properties contained in patalah Shiva patalah I to V while Brahmarahasyam a final section that describes the deliverance teachings contained in patalah patalah VI to XI. Analysis of the meaning of the oracle Tutur Bhuwana Kosa  consists of Shiva in Tutur Bhuwana Kosa , Law of Karma and Reincarnation and Deliverance.
Keywords: Tutur, Siwa, Semiotic